The Effects of Selenium Nanoparticles (SeNPs) on Ruminant - Badgar, Khandsuren; Prokisch, József (Proceedings of the Mongolian Academy of Sciences, 2020)
This study examines the role of selenium and the effects of selenium nanoparticle-enriched food supplementation especially in ruminant animals. Selenium is an essential element that has multiple biological activities. Particularly it is important for many physiological processes, especially for the functions of reproductive and immune systems, metabolism of thyroid hormones, as well as antioxidant defense. Also, the presence of selenium nanoparticles in the diet provide a high content of selenium in milk and meat due to its high bioavailability and low toxicity, which is essential for humans.